JAMIE SULLIVAN'S SELF CONFIDENCE IN NICHOLAS SPARKS NOVEL "A WALK TO REMEMBER" - Novi Sriwulandari; Dede Dicky Prihadi (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2019)
This study discusses the novel of Nicholas Sparks entitled A Walk to Remember. This study tells the story of Jamie Sullivan, a young girl who tries to live her days well and confidently even though she suffers from dangerous leukemia. This research was focused on the self-confidence of female character Jamie Sullivan in dealing with various things in the novel story. This research describes the character of Jamie Sullivan based on observations on novel stories, to obtain accurate and more complete data. This research was supported by several theories from experts so that the data obtained becomes more focused and the researcher also reads the novel more than once so that all data can be more complete. This research can conclude that confidence in the character of Jamie Sullivan is very influential in the storyline. Self-confidence can also play an important role in daily life. The relationship between family or parents with children also greatly affects the formation of the child's character. There are many in this novel that has not been examined. The researcher hopes this research can help further research both in the same novel or different but related.Keyword: Self-Confidence